MENGGAGAS MANAJEMEN PENDIDIKAN INTEGRATIF - M. NASIHUDDIN (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) Sekolah Tinggi Ilmu Tarbiyah Muhammadiyah Tempurrejo Ngawi, 2020)
Education management is main pillar for advancing educational institutions. But in practice, it is not as simple as one might imagine. There are many challenges and problems that must be handled for the implementation of education management. These challenges will not be overcome if only handled by individuals as an element of education, but all parties must work hand in hand to deal with and resolve these problems. To be sure, conceptually the management of school institutions with integrated educational management is a solution to build quality human resources. For this reason, the conceptual formulation must be continuously modified and developed to find conformity with the needs that are developing at that time